Sacred modernity : nature, environment, and the postcolonial geographies of Sri Lankan nationhood - Jazeel, Tariq (2013)
This book explores the relationships between nature and environment and the contested politics of nationhood in contemporary Sri Lanka.
Keywords: Nationalism -- Sri Lanka; Nature and civilization -- Sri Lanka; Nature -- Social aspects -- Sri Lanka; Nationalism; Nature and civilization; Nature -- Social aspects; Nationalbewusstsein; Natur; Sri Lanka; Sri Lanka